Pisístrato, Héracles e o artesão-pintor Exéquias : a emergência de um ethos ático (TEL Tempo, Espaço e Linguagem, 2021)
Abstract: It was agreed to establish Heracles as a secondary heroic deity in the Greek social imagination, compared to Theseus. In this article we will prioritize the image of Heracles as a model of political propaganda for Peisistratus. We will interpret the hero as the reflection of the ruler and his adventures, in the Attic vessels as a strategy and emergence of a new ethos (way of life), highlighted by the artisan-painters, during the Athenian archaic tyranny. Keywords: Tyranny; Peisistratus; Heracles; politics and propaganda